Comparative Analysis of Anecdotes in English and Uzbek (On the Example of a Family) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article examines the comparative analysis of family anecdotes in Uzbek and English. Similarities and differences in the themes, structure, and cultural characteristics of anecdotes are explored. Analysis shows how humor reflects family values in different cultures.